Analisis Muraa’t Al-Nadzir pada Surah Ar-Rahman (Study Analisis Ilmu Badi’) - Dea Adinda; Syarifah Aulia; Harun Al Rasyid (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2025)
This research aims to examine the use of the Muro'at al-Nazhir concept in the science of balaghah which is applied to Surah Ar-Rahman in the Al-Qur'an. Muro'at al-Nazhir is a rhetorical technique that emphasizes harmony in meaning, sound, structure, and even contrast of meaning in a text, thereby creating beauty and strengthening the message. Through a text analysis approach, this research identifies various forms of Muro'at al-Nazhir contained in Surah Ar-Rahman, including sound harmony through the repetition of the phrase "فَبِأَيِّ آلَاءِ رَبِّكُمَا تُكَذِّبَانِ" 31 times , harmony of meaning that describes the greatness of Allah and His blessings , harmony of structure through verses that have similar patterns, as well as harmony of opposing meanings that show the contrast between heaven and hell, as well as the creation of humans and jinn from different elements. The research results show that the use of Muro'at al-Nazhir in Surah Ar-Rahman not only adds to the beauty of the language, but also strengthens the spiritual meaning and messages of faith that are conveyed to humans and jinn. It is hoped that this study can deepen understanding of the art of balaghah in the Koran and inspire further study of rhetoric in this Islamic holy book.